MENAKSIR KESETARAAN GENDER DALAM PROFESI OJEK ONLINE WANITA DI KOTA MALANG - Faizal Kurniawan; Siti Fatimah Soenaryo (Universitas Negeri Malang, 2019)
This study examines in depth the academic anxiety that has arisen among academics about the emergence of the phenomenon of women online motorcycle taxi drivers in the city of Malang. As we have realized, the emergence of female online motorcycle taxi drivers has grown along with the development of online transportation in the city of Malang. From the interview data obtained, starting in 2016 since online transportation has grown in Malang, at least almost 30% growth in recruitment of women online motorcycle taxi drivers. This research uses the case study method. The thesis of this research is the rise the opinion for the gender context itself that the rationality of professional voters as an online motorcycle taxi is not only from economic reasons alone but also the existence of social dynamics housing that occurs in the community. For Foucault, gender phenomena can be said to be a discourse that will later develop the concept of culture. Its idealism and romanticism, women need jobs not only as economic demands, but also gender shifts that women do not only take care of homework. James Coleman sees in the perspective rationality that the choice to be an online motorcycle taxi driver is a